Effective Dose Titration of Fentanyl Sublingual Spray in Patients With Breakthrough Cancer Pain. Issue 8 (28th October 2015) - Rauck, Richard; Bull, Janet; Parikh, Neha; Dillaha, Larry; Stearns, Lisa
Abstract: Objective: To further describe effective dose titration of fentanyl sublingual spray to treat breakthrough cancer pain (BTCP) during the 26‐day open‐label titration phase of a phase 3, randomized, double‐blind, placebo‐controlled study. Methods: Opioid‐tolerant patients with 1 to 4 episodes of BTCP per day were enrolled. For randomization into double‐blind treatment, patients must have titrated to a dose (100 to 1, 600 mcg) providing effective analgesia for 2 consecutive BTCP episodes. The Treatment Satisfaction Questionnaire for Medication was administered at baseline and at titration end and included a Global Satisfaction domain. Results: Of 130 patients undergoing titration, 98 (75%) achieved pain relief (median dose = 800 mcg). The most common doses that allowed for adequate pain relief were 800 mcg (24.5%) and 1, 200 mcg (20.4%). Of 32 (25%) patients who withdrew from the study, only 3 (2.3%) did not achieve an effective dose. In patients attaining an effective dose, mean Global Satisfaction increased from 54.9 ± 2.1 at baseline to 75.3 ± 1.7 at the end of the titration phase. Seventy‐eight patients (60%) reported ≥ 1 adverse event (AE). Thirty‐three AEs (25.4%) were considered probably related to treatment, with nausea (6.2%) and somnolence (4.6%) most commonly reported. Conclusions: In patients with BTCP, fentanyl sublingual spray can be rapidly and safely titrated to an effective dose, resulting in greater satisfaction with fentanyl sublingual spray than previous BTCP medications.